A method for preparing a PVD nano AlCrN / ZrO2 composite coating for a band saw blade

CN122979825APending Publication Date: 2026-10-27HUBEI SHENTIAN NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611197461.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]中国专利申请号为202110870998.0的专利公开了一种周期性多层结构涂层带锯条及其制备方法,其在带锯条基体表面依次沉积CrN结合层、CrN/AlCrN交替功能层和AlCrN顶层,通过周期性多层结构设计提升涂层的力学性能、韧性和锯切寿命;其不足在于,功能层与顶层均为氮化物,涂层整体不具备防粘隔热功能,锯切易粘材料时仍存在齿面粘刀问题

Benefits of technology

[0022]1)本发明将LaPO4与LaF3复配,形成常温防粘与高温润滑的接力及双弱界面增韧,使涂层在宽温域内兼具低粘屑、低摩擦和优异的抗热震性能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a preparation method of a PVD nanometer AlCrN / ZrO2 composite coating of a band saw blade tooth part, and belongs to the technical field of coated metal materials. The method is characterized by sequentially performing sand blasting, ultrasonic cleaning, drying and IET ion etching cleaning on the tooth part of the band saw blade, then sequentially depositing a CrN base layer, an AlCrN wear-resistant layer and a ZrO2-based anti-sticking and heat-insulating layer on the surface of the tooth part, and cooling in the furnace to obtain the composite coating. The ZrO2-based anti-sticking and heat-insulating layer can contain at least one kind of nanometer second phase of LaPO4 and LaF3, and an oxygen-nitrogen gradient transition layer formed by continuous transition from the AlCrN wear-resistant layer to the ZrO2-based anti-sticking and heat-insulating layer can be formed between the AlCrN wear-resistant layer and the ZrO2-based anti-sticking and heat-insulating layer. Compared with the prior art, the composite coating prepared by the method has the properties of anti-sticking, friction reduction, heat insulation and anti-peeling, has high film-substrate adhesion, has a long sawing life of the band saw blade, and the preparation process is continuous and controllable, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coated metal materials technology, and in particular to a method for preparing a PVD nano-AlCrN / ZrO2 composite coating on the teeth of a band saw blade. Background Technology

[0002] Band saw blades are widely used for sawing and cutting metal materials such as stainless steel, titanium alloys, aluminum alloys, and copper. During the sawing process, the teeth are subjected to high temperature, high pressure, and cyclic impact loads, making them prone to failure problems such as tooth surface adhesion, built-up edge, and rapid tooth tip wear. To improve the wear resistance and service life of the teeth, the industry commonly uses physical vapor deposition technology to deposit hard nitride coatings such as TiN, TiAlN, and AlCrN on the teeth of band saw blades. The high hardness, chemical barrier, and thermal barrier effects of the coating reduce tooth tip wear, thereby improving sawing efficiency and band saw blade life.

[0003] Chinese patent application number 202110870998.0 discloses a periodic multilayer coated band saw blade and its preparation method. It sequentially deposits a CrN bonding layer, an alternating CrN / AlCrN functional layer, and an AlCrN top layer on the surface of the band saw blade substrate. The periodic multilayer structure design improves the mechanical properties, toughness, and sawing life of the coating. However, its drawback is that both the functional layers and the top layer are nitrides, and the overall coating lacks anti-sticking and heat insulation functions, still resulting in tooth surface sticking when sawing easily sticky materials. Chinese patent application number 202111368350.X discloses a periodic multilayer nanostructured nitride hard coated band saw blade and its preparation method. It sequentially deposits an AlTiN bonding layer, an AlTiN / AlCrN-based alternating functional layer, and an AlCrN-based top layer on the substrate surface, and improves the fatigue resistance of the saw blade body through post-treatment sandblasting. However, its drawback is that the coating system is also limited to a nitride multilayer structure, failing to solve the problems of metal adhesion on the tooth surface and heat conduction to the tooth tip during sawing. Chinese patent application number 201210510010.0 discloses a CrAlN / ZrO2 nano-multilayer coating and its preparation method. It uses reactive sputtering to alternately deposit CrAlN and ZrO2 layers on a substrate, so that the coating has both high hardness and high oxidation resistance. Its shortcomings are that the interface between nitride and oxide is abrupt and alternating, resulting in obvious stress concentration at the interface. In addition, the coating is not functionalized to meet the anti-sticking and friction reduction requirements of band saw teeth.

[0004] In summary, existing band saw blade coatings remain at the nitride multilayer structure level, generally lacking effective means to inhibit chip adhesion. Furthermore, existing nitride-oxide composite coatings suffer from problems such as abrupt changes in interface composition, stress concentration, and limited functionality. These coatings are prone to cracking and peeling under alternating hot and cold sawing conditions, and it is difficult to simultaneously achieve anti-sticking and friction reduction. Therefore, there is an urgent need to develop a method for preparing a composite coating for band saw blade teeth that combines anti-sticking, friction reduction, heat insulation, and anti-peeling properties to meet the demands of efficient sawing of difficult-to-machine materials such as stainless steel, titanium alloys, and aluminum alloys. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention aims to provide a method for preparing a PVD nano-AlCrN / ZrO2 composite coating on the teeth of a band saw blade.

[0006] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0007] A method for preparing a PVD nano-AlCrN / ZrO2 composite coating on band saw blade teeth includes the following steps: pre-treating the band saw blade teeth by sandblasting, ultrasonic cleaning, and drying; loading the band saw blade into a furnace, evacuating it, heating it, and then performing IET ion etching cleaning on the teeth; then depositing a CrN underlayer on a chromium target and an AlCrN wear-resistant layer on a chromium-aluminum target; finally, depositing a ZrO2-based anti-sticking and heat-insulating layer on the AlCrN wear-resistant layer surface by reactive sputtering on a zirconium target; and finally removing the blade from the furnace after cooling with the furnace to obtain the PVD nano-AlCrN / ZrO2 composite coating on the band saw blade teeth.

[0008] The ZrO2-based anti-sticking thermal insulation layer further contains at least one of LaPO4 or LaF3 as a nano-second phase, and the total mass fraction of the nano-second phase in the ZrO2-based anti-sticking thermal insulation layer is 3%-10%. When depositing the ZrO2-based anti-sticking thermal insulation layer, co-deposition is performed using zirconium target reactive sputtering and radio frequency sputtering of at least one target material selected from LaPO4 or LaF3. During radio frequency sputtering, the radio frequency power density of the target material is controlled to be 1.0-3.0 W / cm². 2 The argon pressure in the vacuum chamber is 0.8-1.2 Pa.

[0009] The ZrO2-based anti-sticking thermal insulation layer is a ZrO2-LaPO4-LaF3 nanocomposite anti-sticking thermal insulation layer containing two nano-second phases, LaPO4 and LaF3. When depositing the ZrO2-LaPO4-LaF3 nanocomposite anti-sticking thermal insulation layer, the LaPO4 ceramic target RF power supply and the LaF3 target RF power supply are turned on simultaneously, and the three targets are co-deposited by zirconium target reactive sputtering, LaPO4 target, and LaF3 target RF sputtering.

[0010] In the ZrO2-LaPO4-LaF3 nanocomposite anti-stick heat insulation layer, the mass ratio of LaPO4 to LaF3 is 1:2-2:1, and the total mass fraction of LaPO4 and LaF3 is 3%-10%.

[0011] After the AlCrN wear-resistant layer is deposited and before the ZrO2-based anti-sticking and heat-insulating layer is deposited, the chromium-aluminum target is not turned off. By continuously reducing the nitrogen flow rate and continuously increasing the oxygen flow rate, and simultaneously increasing the zirconium target current and decreasing the chromium-aluminum target current, an oxygen-nitrogen gradient transition layer that continuously transforms from AlCrN to ZrO2 is formed on the surface of the AlCrN wear-resistant layer. The thickness of the oxygen-nitrogen gradient transition layer is 0.2-0.4 μm. The ZrO2-based anti-sticking and heat-insulating layer is deposited on the surface of the oxygen-nitrogen gradient transition layer.

[0012] The formation process of the oxygen-nitrogen gradient transition layer is as follows: within 10-20 minutes, the nitrogen flow rate is continuously and uniformly reduced from 700-900 sccm to 0, while the oxygen flow rate is simultaneously and uniformly increased from 0 to 300-500 sccm. At the same time, the zirconium target current is continuously and uniformly increased from 0 to 130-170 A, the chromium-aluminum target current is continuously and uniformly reduced from 150-200 A to 0, and the bias voltage amplitude is continuously adjusted from 90 V to 100-110 V.

[0013] The ZrO2-based anti-sticking thermal insulation layer is deposited using an oxygen metering pulse modulation process. This involves a modulation cycle of 20-40 seconds. In the first half of each cycle, the oxygen flow rate is set to 400-500 sccm, the zirconium target current to 130-150 A, and the bias voltage amplitude to 70-90 V. In the second half of each cycle, the oxygen flow rate is set to 700-800 sccm, the zirconium target current to 160-180 A, and the bias voltage amplitude to 110-130 V. The switching time of the bias voltage amplitude lags behind the switching time of the oxygen flow rate by 2-8 seconds. After cyclic deposition, the oxygen flow rate is fixed at 750-900 sccm and the bias voltage amplitude is fixed at 60-80 V for continued deposition, forming a fully oxidized, dense ZrO2 surface layer.

[0014] After the ZrO2-based anti-sticking heat insulation layer is deposited, the bias voltage amplitude is reduced to 50-70V, the oxygen flow rate is increased to 650-750sccm, and the zirconium target current is maintained at 130-170A. A pure ZrO2 sealing layer is then deposited on the surface of the ZrO2-based anti-sticking heat insulation layer for 3-8 minutes. The thickness of the resulting pure ZrO2 sealing layer is 0.05-0.15μm.

[0015] The IET ion etching and cleaning process involves introducing argon gas at a flow rate of 150-250 sccm into the vacuum chamber, turning on the pulse bias power supply, setting the bias amplitude to 120-180V and the duty cycle to 40%-60%, and etching and cleaning the band saw blade teeth for 15-25 minutes. The CrN underlayer deposition process involves adjusting the bias amplitude to 50-70V, introducing nitrogen gas at a flow rate of 200-400 sccm, setting the chromium target current to 120-180A, controlling the pressure in the vacuum chamber to 0.4-0.8Pa, and depositing for 15-25 minutes, resulting in a CrN underlayer thickness of 0.15-0.25μm.

[0016] The AlCrN wear-resistant layer was deposited by adjusting the bias voltage amplitude to 80-100V, introducing nitrogen gas at a flow rate of 600-1000 sccm, setting the chromium-aluminum target current to 150-220A, controlling the vacuum chamber pressure to 1.2-1.8Pa, and the deposition time to 50-70 minutes, resulting in an AlCrN wear-resistant layer thickness of 2.0-2.8μm. The ZrO2-based anti-sticking and heat-insulating layer was deposited with a bias voltage amplitude of 100-140V, an argon gas flow rate of 80-120 sccm, an oxygen flow rate of 500-700 sccm, a zirconium target current of 130-170A, and a vacuum chamber pressure of 0.8-1.2Pa; the total thickness of the resulting composite coating was 3.5-4.5μm.

[0017] In this invention, IET ion etching cleaning is short for ion etching technology. Specifically, it refers to: argon gas is introduced into a vacuum chamber as the working gas, the band saw blade workpiece is used as the cathode and the vacuum chamber wall is used as the anode, and a pulsed bias power supply is used to excite argon gas between the workpiece and the vacuum chamber wall to generate glow discharge plasma. Argon ions are accelerated by the pulsed bias electric field and directionally bombard the surface of the band saw blade teeth. Adsorbed contaminants, residual oxides and micro-oxide layers on the tooth surface are removed through physical sputtering, and the tooth surface is activated. This cleaning method is performed in situ in the same vacuum chamber before coating deposition and does not involve chemical etching media.

[0018] This invention first discovered that in a conventional three-layer system consisting of a CrN underlayer, an AlCrN wear-resistant layer, and a ZrO2 anti-adhesion and heat-insulating layer, the interface between AlCrN and ZrO2 is abruptly different between nitrides and oxides. This interface easily leads to stress concentration and becomes a crack initiation site. Furthermore, the pure ZrO2 top layer has a single columnar crystal structure with grain boundaries extending throughout the entire layer thickness, lacking both methods to suppress chip adhesion and methods to hinder crack propagation. Therefore, this invention introduces an oxygen-nitrogen gradient transition layer, oxygen stoichiometric pulse modulation, a pure ZrO2 sealing layer, and a LaPO4 or LaF3 nano-second phase at the interface, surface, and grain boundaries, respectively, to directionally eliminate the aforementioned interface, surface, and grain boundary defects, thus solving the problems of insufficient coating adhesion, easy cracking, and chip adhesion wear.

[0019] This invention further reveals that when LaPO4 is added alone, its chemical inertness and low wettability only inhibit the adhesion and initiation of chips on the tooth surface, but it lacks the ability to improve the sliding friction of chips already pressed onto the rake face. When LaF3 is added alone, it only softens and forms a lubricating film after the friction temperature rises at the tooth tip, resulting in weak anti-sticking ability at room temperature, and a large difference in thermal expansion compared to ZrO2. Therefore, this invention, while keeping the total amount of the second phase constant, combines LaPO4 and LaF3 in a certain proportion and co-deposits them with a zirconium target, so that room temperature anti-sticking and high temperature lubrication are combined in the functional temperature range, and the two types of weak interfaces deflect and passivate cracks together, solving the problem of insufficient function of a single second phase.

[0020] This invention further discovers that while the compounding scheme addresses adhesion, friction, and crack penetration issues within the top layer, the interface between the wear-resistant layer and the compounded top layer remains a point of abrupt changes in composition and stress, making it a weak point for coating failure under alternating hot and cold sawing conditions. Therefore, this invention inserts an oxygen-nitrogen gradient transition layer between the wear-resistant layer and the compounded top layer, allowing for a continuous transition in composition, crystal structure, and thermal expansion behavior from nitrides to oxides. This creates a relay effect of interface protection and bulk toughening, resolving the issues of easy coating peeling and the difficulty in maintaining stable anti-sticking and friction-reducing functions throughout the entire service life.

[0021] Compared with the prior art, the present invention has the following beneficial technical effects:

[0022] 1) This invention combines LaPO4 and LaF3 to form a combination of room temperature anti-sticking and high temperature lubrication, as well as toughening through a double weak interface, so that the coating has low chip adhesion, low friction and excellent thermal shock resistance over a wide temperature range.

[0023] 2) The oxygen-nitrogen gradient transition layer of the present invention eliminates the abrupt changes in composition and stress between nitrides and oxides, significantly improves the adhesion between the film and the substrate, and makes the coating less prone to cracking and peeling under alternating hot and cold conditions, thus extending the service life of the band saw blade.

[0024] 3) The preparation process of the present invention is completed continuously in the same vacuum furnace without the need for additional special equipment. The process flow is short, the parameters are controllable and highly repeatable, making it suitable for the industrial mass production of coatings on band saw teeth. Detailed Implementation

[0025] The sources or parameters of some substances are as follows:

[0026] Band saw blade body: Commercially available bimetal band saw blade, with M42 high-speed steel teeth and spring steel backing, and specifications of 27mm width, 0.9mm thickness, and 4 / 6TPI tooth pitch.

[0027] Chromium target: Commercially available metallic chromium sputtering targets with a purity of not less than 99.9%.

[0028] Chromium-aluminum target: Commercially available chromium-aluminum alloy sputtering target with an aluminum-chromium atomic ratio of Al:Cr=70:30 and a purity of not less than 99.9%.

[0029] Zirconium target: Commercially available metallic zirconium sputtering targets with a purity of not less than 99.9%.

[0030] Lanthanum phosphate target: A ceramic target material made by molding and sintering commercially available LaPO4 powder with a purity of not less than 99.9% and a relative density of not less than 90%.

[0031] Lanthanum fluoride target: Commercially available LaF3 sputtering target with a purity of not less than 99.9%.

[0032] In the embodiments and comparative examples of this invention, all raw materials are commercially available products.

[0033] In this invention, the nano-second phase refers to second-phase particles dispersed in the ZrO2 matrix with an average particle size of 5-100 nm; the nano-composite anti-sticking and heat-insulating layer refers to a composite layer in which the average grain size of the ZrO2 matrix is ​​5-50 nm and the nano-second phase is distributed within the ZrO2 grains and grain boundaries; the PVD nano-AlCrN / ZrO2 composite coating refers to a composite coating in which the average grain size of each layer of CrN, AlCrN and ZrO2 matrix constituting the coating is in the range of 5-100 nm.

[0034] In this invention, both the ZrO2-based anti-sticking and heat-insulating layer and the pure ZrO2 sealing layer are identified by X-ray diffraction as being predominantly tetragonal zirconium oxide, with a tetragonal phase content of not less than 80%, and the remainder being cubic phase and a small amount of monoclinic phase. The average grain size of the ZrO2 matrix in this invention is 5-50 nm, which is lower than the critical grain size for the spontaneous transformation from tetragonal to monoclinic phase. The tetragonal phase remains stable within the range of room temperature to service temperature due to the nanocrystal size effect. The residual compressive stress within the film layer plays an auxiliary stabilizing role for the tetragonal phase. Therefore, this invention does not require the introduction of stabilizers such as Y2O3. The tooth tip temperature during band saw cutting and the thermal shock test temperature are both lower than the temperature of the reversible phase transformation between the monoclinic and tetragonal phases. No phase transformation accompanied by volume effects occurs within the service temperature range. This is the premise for the ZrO2-based top layer of this invention to maintain structural stability during thermal cycling.

[0035] Example 1

[0036] A method for preparing a PVD nano-AlCrN / ZrO2 composite coating on the teeth of a band saw blade is as follows:

[0037] S1. Substrate pretreatment: Take the band saw blade to be coated and sandblast its teeth to remove the oxide layer, rust and attached dirt on the surface of the teeth and form a uniform and clean surface; after sandblasting, place the band saw blade in an ultrasonic cleaner for 30 minutes and dry it after cleaning. After the surface of the band saw blade is completely dry, it is composite-wound according to the vacuum coating clamping requirements so that the teeth of the band saw blade can be evenly exposed in the subsequent processing.

[0038] S2. Loading, Vacuuming, and Heating: Load the completed composite-wound band saw blade into the workpiece position within the vacuum chamber. Start the vacuum pump to evacuate the chamber and set the workpiece rotation speed to 2 rpm. Heat the vacuum chamber until the temperature reaches 380℃ and the pressure drops to 5.0 × 10⁻⁶. -3 After Pa, maintain the temperature and proceed to the next step of processing;

[0039] S3. Ion etching cleaning: Argon gas with a flow rate of 200 sccm is introduced into the vacuum chamber, the pulse bias power supply is turned on, the bias amplitude is set to 150V and the duty cycle is 50%, and the band saw blade teeth are subjected to IET ion etching cleaning for 20 minutes to further remove adsorbed contaminants and micro-oxide layers on the surface of the band saw blade and to activate the surface of the teeth.

[0040] S4. CrN underlayer deposition: After ion etching and cleaning, the bias voltage amplitude is adjusted to 60V, nitrogen gas with a flow rate of 300sccm is introduced into the vacuum chamber, the chromium target is turned on and the chromium target current is set to 150A, the pressure in the vacuum chamber is controlled to 0.6Pa, and CrN underlayer is deposited on the surface of the band saw teeth for 20 minutes. The thickness of the obtained CrN underlayer is 0.2μm.

[0041] S5. Deposition of AlCrN wear-resistant layer: After the CrN underlayer deposition is completed, the bias voltage amplitude is adjusted to 90V, nitrogen gas with a flow rate of 800sccm is introduced into the vacuum chamber, the chromium aluminum target is turned on and the chromium aluminum target current is set to 180A, the pressure in the vacuum chamber is controlled to 1.5Pa, and the AlCrN wear-resistant layer is deposited on the surface of the CrN underlayer. The deposition time is 60 minutes, and the thickness of the obtained AlCrN wear-resistant layer is 2.5μm.

[0042] S6. Deposition of ZrO2 anti-sticking and heat insulation layer: After the AlCrN wear-resistant layer is deposited, the bias voltage amplitude is adjusted to 120V, argon gas with a flow rate of 100sccm and oxygen gas with a flow rate of 600sccm are introduced into the vacuum chamber, the zirconium target is turned on and the zirconium target current is set to 150A, the pressure in the vacuum chamber is controlled to be 0.9Pa, and the ZrO2 anti-sticking and heat insulation layer is deposited on the surface of the AlCrN wear-resistant layer by reactive sputtering. The deposition time is 30 minutes, and the thickness of the obtained ZrO2 anti-sticking and heat insulation layer is 1.3μm.

[0043] S7. Cooling and unloading: After the ZrO2 anti-sticking and heat insulation layer is deposited, the zirconium target, bias power supply, argon and oxygen are turned off in sequence to keep the vacuum chamber in a vacuum state, so that the band saw blade cools with the furnace; after the temperature in the vacuum chamber drops below 100℃, the gas is released into the vacuum chamber and the band saw blade is taken out, thus obtaining the PVD nano AlCrN / ZrO2 composite coating on the teeth of the band saw blade.

[0044] Example 2

[0045] The preparation method of a PVD nano-AlCrN / ZrO2 composite coating for band saw teeth is basically the same as that in Example 1, except that step S6 is different.

[0046] Step S6 is as follows: Deposition of the oxygen-nitrogen gradient transition layer: After the AlCrN wear-resistant layer is deposited, without shutting off the chromium-aluminum target, the nitrogen flow rate is continuously and uniformly reduced from 800 sccm to 0 within 15 minutes, while simultaneously and uniformly increasing the oxygen flow rate from 0 to 400 sccm. Simultaneously, the zirconium target current is continuously and uniformly increased from 0 to 150 A, and the chromium-aluminum target current is continuously and uniformly reduced from 180 A to 0. The bias voltage amplitude is continuously adjusted from 90 V to 100 V. During the transition, the pressure inside the vacuum chamber is controlled from 1.5... The pressure was uniformly transitioned from Pa to 0.9 Pa, resulting in an oxygen-nitrogen gradient transition layer with a thickness of 0.3 μm. After the oxygen-nitrogen gradient transition layer was deposited, the bias voltage amplitude was adjusted to 120 V, and argon gas with a flow rate of 100 sccm and oxygen gas with a flow rate of 600 sccm were introduced into the vacuum chamber. The zirconium target current was maintained at 150 A, and the pressure in the vacuum chamber was controlled at 0.9 Pa. A ZrO2 anti-sticking and heat-insulating layer was deposited on the surface of the oxygen-nitrogen gradient transition layer by reactive sputtering. The thickness of the ZrO2 anti-sticking and heat-insulating layer was controlled to be 1.0 μm by the deposition time.

[0047] Example 3

[0048] The preparation method of a PVD nano-AlCrN / ZrO2 composite coating for band saw teeth is basically the same as that in Example 1, except that step S6 is different.

[0049] Step S6 is as follows: Deposition of oxygen metering modulated ZrO2 anti-sticking and heat insulation layer: After the AlCrN wear-resistant layer is deposited, argon gas with a flow rate of 100 sccm is introduced into the vacuum chamber, the zirconium target is turned on, and the pressure in the vacuum chamber is controlled at 0.9 Pa. Pulse deposition is performed with a modulation cycle of 30 seconds: In the first half of each cycle, the oxygen flow rate is set to 450 sccm, the zirconium target current is set to 140 A, and the bias voltage amplitude is set to 80 V; in the second half of each cycle, the oxygen flow rate is set to 750 sccm, the zirconium target current is set to 170 A, and the bias voltage amplitude is set to 120 V; the switching time of the bias voltage amplitude lags behind the switching time of the oxygen flow rate by 5 seconds. After pulse deposition is performed in this manner for 28 minutes, the oxygen flow rate is fixed at 800 sccm and the bias voltage amplitude is fixed at 70 V, and deposition continues for 2 minutes to form a completely oxidized dense ZrO2 surface layer. The total thickness of the obtained oxygen metering modulated ZrO2 anti-sticking and heat insulation layer is 1.3 μm.

[0050] The bias switching lags behind the oxygen switching in order to compensate for the response delay of oxygen transmission to the substrate surface through the pipeline, so that the bias modulation matches the actual change of oxygen partial pressure on the substrate surface, avoids excessive bombardment of the not-yet-fully-oxidized film by ions when the bias increases, thereby reducing film defects, stabilizing discharge and regulating the stress of the modulation interface.

[0051] Example 4

[0052] The preparation method of a PVD nano-AlCrN / ZrO2 composite coating for band saw teeth is basically the same as that in Example 1, except that step S6 is different.

[0053] Step S6 is as follows: Deposition of ZrO2 anti-sticking and heat insulation layer: After the AlCrN wear-resistant layer is deposited, the bias voltage amplitude is adjusted to 120V, argon gas with a flow rate of 100sccm and oxygen gas with a flow rate of 600sccm are introduced into the vacuum chamber, the zirconium target is turned on and the zirconium target current is set to 150A, and the pressure in the vacuum chamber is controlled to 0.9Pa. The ZrO2 anti-sticking and heat insulation layer is deposited on the surface of the AlCrN wear-resistant layer by reactive sputtering for 28 minutes. The thickness of the obtained ZrO2 anti-sticking and heat insulation layer is 1.2μm. After the ZrO2 anti-sticking and heat insulation layer is deposited, the bias voltage amplitude is reduced from 120V to 60V, the oxygen flow rate is increased from 600sccm to 700sccm, the zirconium target current is kept at 150A, and the pressure in the vacuum chamber is controlled to 0.9Pa. A pure ZrO2 sealing layer is then deposited on the surface of the ZrO2 anti-sticking and heat insulation layer for 5 minutes. The thickness of the obtained sealing layer is 0.1μm.

[0054] Example 5

[0055] The preparation method of a PVD nano-AlCrN / ZrO2 composite coating for band saw teeth is basically the same as that in Example 1, except that step S6 is different.

[0056] Step S6 is as follows: Deposition of ZrO2-LaPO4 nanocomposite anti-sticking and heat-insulating layer: After the AlCrN wear-resistant layer is deposited, the bias voltage amplitude is adjusted to 120V, argon gas with a flow rate of 100sccm and oxygen gas with a flow rate of 600sccm are introduced into the vacuum chamber, the zirconium target is turned on and the zirconium target current is set to 150A, and the LaPO4 ceramic target RF power supply is turned on and the RF power density is set to 2.8W / cm². 2 The pressure in the vacuum chamber was controlled at 0.9 Pa. A ZrO2-LaPO4 nanocomposite anti-sticking and heat-insulating layer was deposited on the surface of the AlCrN wear-resistant layer by co-deposition of zirconium target reactive sputtering and LaPO4 target radio frequency sputtering. The deposition time was 30 minutes. The mass fraction of LaPO4 in the resulting composite layer was 6%, and the thickness of the composite layer was 1.3 μm.

[0057] Example 6

[0058] The preparation method of a PVD nano-AlCrN / ZrO2 composite coating for band saw teeth is basically the same as that in Example 1, except that step S6 is different.

[0059] Step S6 is as follows: Deposition of ZrO2-LaF3 nanocomposite anti-sticking and heat-insulating layer: After the AlCrN wear-resistant layer is deposited, the bias voltage amplitude is adjusted to 120V, argon gas with a flow rate of 100sccm and oxygen gas with a flow rate of 600sccm are introduced into the vacuum chamber, the zirconium target is turned on and the zirconium target current is set to 150A, and the LaF3 target RF power supply is turned on and the RF power density is set to 2.8W / cm². 2 The pressure in the vacuum chamber was controlled at 0.9 Pa. A ZrO2-LaF3 nanocomposite anti-sticking and heat-insulating layer was deposited on the surface of the AlCrN wear-resistant layer by reactive sputtering with a zirconium target and radio frequency sputtering with a LaF3 target. The preferential sputtering loss of fluorine was suppressed by controlling the radio frequency power density and argon pressure. The deposition time was 30 minutes. The mass fraction of LaF3 in the resulting composite layer was 6%, and the thickness of the composite layer was 1.3 μm.

[0060] In this embodiment, the radio frequency power density of the LaF3 target is 2.8 W / cm². 2 The argon pressure in the vacuum chamber is 0.9 Pa. At this power density, the sputtering energy density of the LaF3 target surface is relatively low, which can reduce the preferential sputtering of fluorine relative to lanthanum; at the same time, the argon pressure weakens the energy of particles bombarding the film through collision scattering of sputtered particles, suppressing the backsputtering loss of fluorine in the deposited film. Under these conditions, the measured mass fraction of LaF3 in the film can reach more than 85% of the theoretical doping amount. When the RF power density exceeds 3.0 W / cm²...2 At that time, the preferential sputtering of fluorine and the back sputtering of the film layer are significantly aggravated, and the LaF3 content in the film layer decreases significantly; therefore, the present invention controls the radio frequency power density to 1.0-3.0 W / cm² and the argon pressure to 0.8-1.2 Pa to effectively suppress the preferential sputtering loss of fluorine.

[0061] Example 7

[0062] The preparation method of a PVD nano-AlCrN / ZrO2 composite coating for band saw teeth is basically the same as that in Example 1, except that step S6 is different.

[0063] Step S6 is as follows: Deposition of ZrO2-LaPO4-LaF3 nanocomposite anti-sticking and heat-insulating layer: After the AlCrN wear-resistant layer is deposited, the bias voltage amplitude is adjusted to 120V, argon gas with a flow rate of 100sccm and oxygen gas with a flow rate of 600sccm are introduced into the vacuum chamber, the zirconium target is turned on and the zirconium target current is set to 150A, and the LaPO4 ceramic target RF power supply and LaF3 target RF power supply are turned on at the same time, and the RF power density of both the LaPO4 target and LaF3 target is set to 1.4W / cm². 2 The pressure in the vacuum chamber was controlled at 0.9 Pa. A three-target co-deposition process was carried out using zirconium target reactive sputtering, LaPO4 target, and LaF3 target RF sputtering. The preferential sputtering loss of fluorine was suppressed by controlling the RF power density of the LaF3 target and the argon pressure. A ZrO2-LaPO4-LaF3 nanocomposite anti-sticking and heat-insulating layer was deposited on the surface of the AlCrN wear-resistant layer. The deposition time was 30 minutes. The mass fraction of LaPO4 in the resulting composite layer was 3%, the mass fraction of LaF3 was 3%, and the thickness of the composite layer was 1.3 μm.

[0064] Example 8

[0065] The preparation method of a PVD nano-AlCrN / ZrO2 composite coating for band saw teeth is basically the same as that in Example 1, except that step S6 is different.

[0066] Step S6 is as follows: Deposition of the oxygen-nitrogen gradient transition layer: After the AlCrN wear-resistant layer is deposited, without shutting down the chromium-aluminum target, the nitrogen flow rate is continuously and uniformly reduced from 800 sccm to 0 within 15 minutes, while the oxygen flow rate is simultaneously and uniformly increased from 0 to 400 sccm. Simultaneously, the zirconium target current is continuously and uniformly increased from 0 to 150 A, and the chromium-aluminum target current is continuously and uniformly reduced from 180 A to 0. The bias voltage amplitude is continuously adjusted from 90 V to 100 V. During the transition, the pressure inside the vacuum chamber is controlled. The pressure was uniformly transitioned from 1.5 Pa to 0.9 Pa, resulting in an oxygen-nitrogen gradient transition layer with a thickness of 0.3 μm. After the oxygen-nitrogen gradient transition layer was deposited, the bias amplitude was adjusted to 120 V, and argon gas at a flow rate of 100 sccm and oxygen gas at a flow rate of 600 sccm were introduced into the vacuum chamber. The zirconium target was turned on and the zirconium target current was set to 150 A. Simultaneously, the RF power supplies for the LaPO4 ceramic target and the LaF3 target were turned on, and the RF power densities of both the LaPO4 and LaF3 targets were set to 1.4 W / cm². 2 The pressure in the vacuum chamber was controlled at 0.9 Pa. A three-target co-deposition was carried out by zirconium target reactive sputtering, LaPO4 target, and LaF3 target radio frequency sputtering. The preferential sputtering loss of fluorine was suppressed by controlling the radio frequency power density of LaF3 target and argon pressure. A ZrO2-LaPO4-LaF3 nanocomposite anti-sticking and heat insulation layer was deposited on the surface of oxygen-nitrogen gradient transition layer. The thickness of the resulting composite layer was controlled to be 1.0 μm by the deposition time. The mass fraction of LaPO4 in the resulting composite layer was 3% and the mass fraction of LaF3 was 3%.

[0067] Test Example 1

[0068] Chip adhesion rate and sawing resistance test: Band saw blades with composite coatings on the teeth, prepared in Examples 1-8, were used. All blades were bimetallic, 27mm wide, 0.9mm thick, with a tooth pitch of 4 / 6 TPI. The base material and tooth shape were identical, and the total coating thickness was 4.0μm. Each band saw blade was mounted on the same horizontal band saw, and 50mm diameter 304 stainless steel bars were used for sawing. Dry sawing was performed without coolant. The workpiece was fixed on a three-dimensional force gauge mounted on the band saw table to record the main cutting force in real time. An infrared thermal imager calibrated with emissivity was used to continuously measure the tooth tip temperature at the point where the workpiece was just cut. The sawing speed was set at 40m / min, and the feed pressure was kept constant. Each sample was continuously sawed, with a sawing area of ​​100cm². 2The machine was stopped, and 10 saw teeth were randomly selected from the sawing section. The rake face was observed under 200x scanning electron microscopy, and the iron element signal on the rake face was scanned using energy dispersive spectroscopy. The percentage of the area of ​​the metal adhesion region on the rake face to the total area of ​​the rake face was calculated using image analysis software as the chip adhesion rate under the cumulative sawing area. At the same time, the average value of the main cutting force recorded by the force gauge in the stable section of the sawing section was taken as the sawing resistance. Each embodiment was tested repeatedly with 3 band saw blades and the average value was taken. The results are shown in Table 1.

[0069] Table 1

[0070] Test Plan Average temperature at the tooth tip (°C) Debris adhesion rate (%) Cutting resistance (N) Example 1 618 22.5 486 Example 2 612 20.8 472 Example 3 598 19.4 465 Example 4 608 19.8 470 Example 5 588 11.2 425 Example 6 585 15.6 432 Example 7 563 7.3 385 Example 8 552 6.1 371

[0071] Test Example 2

[0072] Thermal shock cycling test:

[0073] Each band saw blade segment containing 20 complete saw teeth was cut from the band saw blades prepared in Examples 1-8 as a sample, with a total coating thickness of 4.0 μm. Each sample was placed in a box-type resistance furnace, heated to 700°C in air atmosphere and held for 10 minutes. After removal, it was quickly immersed in deionized water at 25°C to quench and cool to room temperature, which was recorded as one thermal shock cycle. After 10 cycles, the sample was placed under a 200x optical microscope to observe the coating of each of the 20 saw teeth. The failure criterion for the sample was that the coating peeled off any tooth and the peeled area exceeded 5% of the coating area of ​​that tooth, or that the coating showed a crack that penetrated to the film-substrate interface. The number of thermal shock cycles that each sample underwent to reach the failure criterion was recorded. If the sample did not fail after 100 cycles, the test was terminated and recorded as more than 100 cycles. Five samples were tested in parallel for each example and the average value was taken. The results are shown in Table 2.

[0074] Table 2

[0075] Test Plan Number of thermal shock failure cycles (times) Example 1 24 Example 2 46 Example 3 38 Example 4 30 Example 5 42 Example 6 34 Example 7 58 Example 8 86

[0076] In Example 1, the AlCrN wear-resistant layer and the ZrO2 anti-adhesion and heat-insulating layer form abrupt interfaces between nitrides and oxides. These two layers differ significantly in crystal structure, elastic modulus, and thermal expansion behavior, making stress concentration at the interface a potential source of crack initiation. Furthermore, the pure ZrO2 top layer has a single columnar crystal structure with grain boundaries extending throughout the entire layer thickness, lacking both methods to suppress chip adhesion and hinder crack propagation. Example 2 addresses this by using an oxygen-nitrogen gradient transition layer to ensure a continuous transition from nitrides to oxides, mitigating the abrupt stress change at the interface. Example 3 introduces nanoscale modulation interfaces and oxygen vacancies within the top layer through oxygen stoichiometry, further hindering heat conduction to the tooth tip while deflecting cracks. Example 4 reduces surface defects and adhesion sites through a sealing porous layer. Examples 5 and 6 introduce LaPO4 or LaF3 nanoscale second phases into the ZrO2 grain boundaries, utilizing their low wetting properties or high-temperature lubrication properties to suppress chip adhesion, reduce friction, and deflect cracks through weak interfaces. Therefore, Examples 2-6 respectively targeted improvements to the interface, surface, or grain boundary defects of Example 1, and all performance aspects were superior to those of Example 1.

[0077] Anti-adhesion and friction reduction are two different aspects of tooth surface failure. When LaPO4 is added alone, its chemical inertness and low wettability can only inhibit the adhesion and initiation of chips on the tooth surface, but it has little effect on improving the sliding friction of chips already pressed onto the rake face. When LaF3 is added alone, it needs to soften and form a low-shear lubricating film after the friction temperature rises at the tooth tip, and its anti-adhesion ability at room temperature is weak. Moreover, the thermal expansion difference between LaF3 and ZrO2 is large, and the improvement of the coating's thermal shock resistance is limited when LaF3 is introduced at a high content alone. In Example 7, under the premise of keeping the total amount of the second phase unchanged, LaPO4 is used to perform the anti-adhesion function at room temperature, and LaF3 is used to perform the lubrication and friction reduction function at high temperature. The two form a relay in the functional temperature range. At the same time, both weak interfaces of ZrO2 / LaPO4 and ZrO2 / LaF3 can deflect and passivate cracks. Moreover, LaPO4 and LaF3 are both lanthanum-containing compounds, which are compatible with each other at the interface, do not react, and do not form a brittle third phase, and can coexist stably in the ZrO2 matrix. Therefore, Example 7 is superior to both single-addition examples in terms of anti-adhesion, friction reduction, and thermal shock resistance, demonstrating the synergistic effect of the compound. It should be noted that the thermal expansion mismatch between LaPO4 and LaF3 and ZrO2 does not translate into macroscopic interfacial thermal stress in this invention: on the one hand, the total mass fraction of the second phase is no higher than 10% and is dispersed at the nanoscale, so the mismatch strain is limited to the nanoscale range and exists only in the form of micro-region compressive stress at grain boundaries, which actually forms a pre-compressive stress constraint for crack initiation; on the other hand, the interfacial energies of the two weak interfaces, ZrO2 / LaPO4 and ZrO2 / LaF3, are different. When the crack extends to the interface, it deflects, bifurcates, and becomes passivated, the crack path is significantly extended, and the extension energy is repeatedly dissipated; after compounding, the ZrO2 matrix grain size is further refined and the number of grain boundaries increases, providing more weak interfacial sites for crack deflection. Therefore, the compound system still exhibits better thermal shock resistance than the single-addition system even when thermal expansion mismatch exists.

[0078] Example 7 only addressed the adhesion, friction, and crack penetration issues within the ZrO2-based top layer. However, the interface between the AlCrN wear-resistant layer and the top layer remained a point of abrupt changes in composition and stress. Under alternating hot and cold sawing conditions, this interface remained a weak point for stress concentration and crack initiation, and the toughening effect of the top layer could not compensate for the inherent bonding defects of the interface. Example 8 inserted an oxygen-nitrogen gradient transition layer between the wear-resistant layer and the composite top layer, allowing for a continuous transition in composition, crystal structure, and thermal expansion behavior from nitrides to oxides. This released interfacial stress, significantly improving the interfacial bonding strength. Cracks were less likely to initiate at the interface and were repeatedly deflected and dissipated by the two weak interfaces after entering the top layer, forming a relay synergy of interfacial protection and bulk toughening. This ensured that the anti-adhesion and friction-reducing functions of the composite top layer remained stable over a longer service life. Therefore, the performance of Example 8 was further superior to that of Example 7.

[0079] Test Example 3

[0080] Nanoscale testing:

[0081] Coating samples were scraped from the teeth of the band saw blades prepared in Examples 1-8, or samples were prepared by simultaneously depositing the processes of each example onto a copper mesh support film for transmission electron microscopy (TEM). The microstructure of the ZrO2-based anti-sticking heat insulation layer was observed under 200,000x TEM. Five fields of view were randomly selected for each example, and the ZrO2 grain size and the particle size of the second phase were statistically analyzed using image analysis software. At least 200 particles were counted for each example, and the average value was taken. X-ray diffraction analysis was performed on the coating samples of each example. The scanning range was 20°-80°, and the scanning step size was 0.02°. The strongest diffraction peak of ZrO2 was selected, and the average grain size of the ZrO2 matrix was calculated using the Scherrer formula. At the same time, the relative content of the tetragonal phase was calculated based on the integrated intensity of the tetragonal, cubic, and monoclinic phase diffraction peaks in the diffraction spectrum. The results are shown in Table 3.

[0082] Table 3

[0083] Test Plan <![CDATA[Average grain size of ZrO2 matrix (nm)]]> Second phase average particle size (nm) Tetragonal phase content (%) Example 1 22 - 82 Example 2 19 - 85 Example 3 14 - 90 Example 4 18 - 86 Example 5 16 28 88 Example 6 17 31 84 Example 7 12 19 91 Example 8 10 16 93

[0084] In Example 3, pulse modulation inhibits continuous grain growth, resulting in finer grains. In Examples 7 and 8, the second phase has a pinning effect on grain boundary migration, further refining the grains. Furthermore, when the total amount of the second phase is the same and the compound dispersion is more uniform, the particle size is smaller. All values ​​fall within the aforementioned 5-100nm range.

Claims

1. A method for preparing a PVD nano-AlCrN / ZrO2 composite coating on the teeth of a band saw blade, characterized in that, The process includes the following steps: pre-treating the band saw blade teeth sequentially with sandblasting, ultrasonic cleaning, and drying; loading the band saw blade into a furnace, evacuating it, and heating it before performing IET ion etching cleaning on the teeth; then, depositing a CrN underlayer on a chromium target and an AlCrN wear-resistant layer on a chromium-aluminum target; finally, using a zirconium target, depositing a ZrO2-based anti-sticking and heat-insulating layer on the AlCrN wear-resistant layer surface via reactive sputtering; and finally, cooling the zirconium target in the furnace before removing it from the furnace to obtain the PVD nano-AlCrN / ZrO2 composite coating on the band saw blade teeth.

2. The preparation method according to claim 1, characterized in that: The ZrO2-based anti-sticking thermal insulation layer further contains at least one of LaPO4 or LaF3 as a nano-second phase, and the total mass fraction of the nano-second phase in the ZrO2-based anti-sticking thermal insulation layer is 3%-10%. When depositing the ZrO2-based anti-sticking thermal insulation layer, co-deposition is performed using zirconium target reactive sputtering and radio frequency sputtering of at least one target material selected from LaPO4 or LaF3. During radio frequency sputtering, the radio frequency power density of the target material is controlled to be 1.0-3.0 W / cm². 2 The argon pressure in the vacuum chamber is 0.8-1.2 Pa.

3. The preparation method according to claim 2, characterized in that: The ZrO2-based anti-sticking thermal insulation layer is a ZrO2-LaPO4-LaF3 nanocomposite anti-sticking thermal insulation layer containing two nano-second phases, LaPO4 and LaF3. When depositing the ZrO2-LaPO4-LaF3 nanocomposite anti-sticking thermal insulation layer, the LaPO4 ceramic target RF power supply and the LaF3 target RF power supply are turned on simultaneously, and the three targets are co-deposited by zirconium target reactive sputtering, LaPO4 target, and LaF3 target RF sputtering.

4. The preparation method according to claim 3, characterized in that: In the ZrO2-LaPO4-LaF3 nanocomposite anti-stick heat insulation layer, the mass ratio of LaPO4 to LaF3 is 1:2-2:1, and the total mass fraction of LaPO4 and LaF3 is 3%-10%.

5. The preparation method according to claim 1, characterized in that: After the AlCrN wear-resistant layer is deposited and before the ZrO2-based anti-sticking and heat-insulating layer is deposited, the chromium-aluminum target is not turned off. By continuously reducing the nitrogen flow rate and continuously increasing the oxygen flow rate, and simultaneously increasing the zirconium target current and decreasing the chromium-aluminum target current, an oxygen-nitrogen gradient transition layer that continuously transforms from AlCrN to ZrO2 is formed on the surface of the AlCrN wear-resistant layer. The thickness of the oxygen-nitrogen gradient transition layer is 0.2-0.4 μm. The ZrO2-based anti-sticking and heat-insulating layer is deposited on the surface of the oxygen-nitrogen gradient transition layer.

6. The preparation method according to claim 5, characterized in that: The formation process of the oxygen-nitrogen gradient transition layer is as follows: within 10-20 minutes, the nitrogen flow rate is continuously and uniformly reduced from 700-900 sccm to 0, while the oxygen flow rate is simultaneously and uniformly increased from 0 to 300-500 sccm. At the same time, the zirconium target current is continuously and uniformly increased from 0 to 130-170 A, the chromium-aluminum target current is continuously and uniformly reduced from 150-200 A to 0, and the bias voltage amplitude is continuously adjusted from 90 V to 100-110 V.

7. The preparation method according to claim 1, characterized in that: The ZrO2-based anti-sticking thermal insulation layer is deposited using an oxygen metering pulse modulation process. This involves a modulation cycle of 20-40 seconds. In the first half of each cycle, the oxygen flow rate is set to 400-500 sccm, the zirconium target current to 130-150 A, and the bias voltage amplitude to 70-90 V. In the second half of each cycle, the oxygen flow rate is set to 700-800 sccm, the zirconium target current to 160-180 A, and the bias voltage amplitude to 110-130 V. The switching time of the bias voltage amplitude lags behind the switching time of the oxygen flow rate by 2-8 seconds. After cyclic deposition, the oxygen flow rate is fixed at 750-900 sccm and the bias voltage amplitude is fixed at 60-80 V for continued deposition, forming a fully oxidized, dense ZrO2 surface layer.

8. The preparation method according to claim 1, characterized in that: After the ZrO2-based anti-sticking heat insulation layer is deposited, the bias voltage amplitude is reduced to 50-70V, the oxygen flow rate is increased to 650-750sccm, and the zirconium target current is maintained at 130-170A. A pure ZrO2 sealing layer is then deposited on the surface of the ZrO2-based anti-sticking heat insulation layer for 3-8 minutes. The thickness of the resulting pure ZrO2 sealing layer is 0.05-0.15μm.

9. The preparation method according to claim 1, characterized in that: The IET ion etching and cleaning process involves introducing argon gas at a flow rate of 150-250 sccm into the vacuum chamber, turning on the pulse bias power supply, setting the bias amplitude to 120-180V and the duty cycle to 40%-60%, and etching and cleaning the band saw blade teeth for 15-25 minutes. The CrN underlayer deposition process involves adjusting the bias amplitude to 50-70V, introducing nitrogen gas at a flow rate of 200-400 sccm, setting the chromium target current to 120-180A, controlling the pressure in the vacuum chamber to 0.4-0.8Pa, and depositing for 15-25 minutes, resulting in a CrN underlayer thickness of 0.15-0.25μm.

10. The preparation method according to claim 1, characterized in that: The AlCrN wear-resistant layer was deposited by adjusting the bias voltage amplitude to 80-100V, introducing nitrogen gas at a flow rate of 600-1000 sccm, setting the chromium-aluminum target current to 150-220A, controlling the vacuum chamber pressure to 1.2-1.8Pa, and the deposition time to 50-70 minutes, resulting in an AlCrN wear-resistant layer thickness of 2.0-2.8μm. The ZrO2-based anti-sticking and heat-insulating layer was deposited with a bias voltage amplitude of 100-140V, an argon gas flow rate of 80-120 sccm, an oxygen flow rate of 500-700 sccm, a zirconium target current of 130-170A, and a vacuum chamber pressure of 0.8-1.2Pa; the total thickness of the resulting composite coating was 3.5-4.5μm.

Citation Information

Patent Citations

  • A CrAlN / ZrO2 nanocoating and its preparation method

    CN103305789B

  • A periodic multilayer coated band saw blade, its preparation method and application

    CN113584438B

  • Periodic multilayer nanostructure nitride hard coating band saw blade and preparation method and application thereof

    CN114196912A